2011
DOI: 10.1038/jidsymp.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Inflammation in Cutaneous Fibrosis: Fibroblast Growth Factor Receptor Deficiency in Keratinocytes as an Example

Abstract: Fibrosis is associated with a variety of skin diseases and causes severe aesthetic and functional impairments. Functional studies in rodents, together with clinical observations, strongly suggest a crucial role of chronic injury and inflammation in the pathogenesis of fibrotic diseases. The phenotype of mice lacking fibroblast growth factor (FGF) receptors 1 and 2 in keratinocytes supports this concept. In these mice, a defect in keratinocytes alone initiated an inflammatory response, which in turn caused kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…Animal studies have demonstrated that chronic inflammation is a critical feature in the pathogenesis of cutaneous fibrosis. 19 Previous surveys have also observed the association of male sex with phymatous rosacea. 20,21 We did not observe a significant association of OC with either ETR or PPR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Animal studies have demonstrated that chronic inflammation is a critical feature in the pathogenesis of cutaneous fibrosis. 19 Previous surveys have also observed the association of male sex with phymatous rosacea. 20,21 We did not observe a significant association of OC with either ETR or PPR.…”
Section: Discussionmentioning
confidence: 98%
“…19 The clinical distinction between facial erythema of rosacea from that due to photodamage is difficult. In this study, central facial distribution of erythema and photographic representations from the NRSEC were used as a guide to case-finding.…”
Section: 24mentioning
confidence: 99%
“…Keratinocytes are critical regulators of fibroblast activity during wound healing, and recent studies suggest that the epidermis can play an active role in dermal fibrosis [6770]. Defects in epidermal integrity can promote fibrosis indirectly by increasing inflammation, which leads to profibrotic stimulation of fibroblasts, or directly by secretion of paracrine factors that regulate fibroblast proliferation and matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also did not observe a granulomatous reaction that could impair contraction. Rather, it seems probable that the alterations in the connective tissue that develop in these mice (Meyer et al, 2011) are responsible for the impaired wound contraction.…”
Section: Discussionmentioning
confidence: 99%